2007
DOI: 10.1021/ic0701460
|View full text |Cite
|
Sign up to set email alerts
|

A Pyrazolate-Supported Fe33-O) Core:  Structural, Spectroscopic, Electrochemical, and Magnetic Study

Abstract: A comparison is made between the structural, spectroscopic, electrochemical, and magnetic properties of pyrazolate versus carboxylate complexes [Fe3(μ3(μ3O)(μ-LL)6Cl3]2− containing the Fe3(μ3-O)-motif. While the Fe3(μ3-O)-cores are structurally indistinguishable in the two types of complexes, their magnetic properties deviate from the expected values as a result of a through-pyrazole contribution to the overall antiferromagnetic exchange with J 1/hc = −80.1 cm−1 and J 2/hc = −72.4 cm−1, or J 1/hc = 70.6 cm−1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
52
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 57 publications
(63 citation statements)
references
References 66 publications
11
52
0
Order By: Relevance
“…[53] Figure 5. [54] Mössbauer spectroscopy, magnetic susceptibility and EPR studies revealed the presence of antiferromagnetic interactions between the iron(III) ions and the achievement of a ground state of S T = 1/2. [30] [M 3 -µ 3 -O(RЈ)] m+ (RЈ = H, Me; m = 4, 5, 7) centred triangles are reported with several transition-metal ions, such as iron(III), cobalt(II/III) and copper(II) ions ( Figure 4c).…”
Section: Polynuclear Compounds Pyrazole Ligands With Non-coordinatingmentioning
confidence: 98%
See 1 more Smart Citation
“…[53] Figure 5. [54] Mössbauer spectroscopy, magnetic susceptibility and EPR studies revealed the presence of antiferromagnetic interactions between the iron(III) ions and the achievement of a ground state of S T = 1/2. [30] [M 3 -µ 3 -O(RЈ)] m+ (RЈ = H, Me; m = 4, 5, 7) centred triangles are reported with several transition-metal ions, such as iron(III), cobalt(II/III) and copper(II) ions ( Figure 4c).…”
Section: Polynuclear Compounds Pyrazole Ligands With Non-coordinatingmentioning
confidence: 98%
“…Molecular structure of [Cu 3 (L1f) 3 ]. [54] In this case, the pyrazole ligands mediate stronger antiferromagnetic interactions than the analogous carboxylates. Compounds X 4 [Fe 3 (µ 3 -O)(L1f) 6 Cl 3 ]Cl 2 (X + = HNEt 3 + , Bu 4 N + , PPh 4 + ) have a structure which resembles the basic carboxylates because of the presence of six pyrazole ligands.…”
Section: Polynuclear Compounds Pyrazole Ligands With Non-coordinatingmentioning
confidence: 99%
“…The eigenvalues returned from the diagonalization routine enters the partition function (in the given field direction), from which the magnetization and susceptibility components are obtained as the first and the second derivatives with respect to the magnetic field. The procedure like this has been successfully applied in fitting the magnetic data for a triangulo-(Et 3 NH) 4 [Fe 3 O(NO 2 -pz) 6 Cl 3 ]Cl 2 complex [46].…”
Section: Perpendicular Eigenvalues Derivatives Substitutionsmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19][20][21][22] The pyrazole heterocycle is a multifunctional group well-suited for this role, and upon deprotonation can provide an additional pair of nitrogen donor atoms that allow it to act as an anionic bridge reminiscent of a carboxylate group. [23,24] Several complexes are known in which pyrazole-TACN hybrid scaffolds support two nickel, copper, or zinc ions with metal separations of 3.5-4.5 Å, leading to their investigation as models for dinuclear metallobiosites. [25][26][27][28][29][30][31][32] In addition to studies focusing on hydrolytic reactivity resembling that mediated by urease, [28,33] phosphoesterases, [26,34,35] and metallo-β-lactamases, [35] these complexes have also been applied in emulating functional and structural aspects of Type 3 (T3) dinuclear copper active sites, such as those found in hemocyanin, tyrosinase, and catechol oxidase.…”
Section: Introductionmentioning
confidence: 99%